The ‘One Health’ Approach to an Epidemic Response - Cherian, Vinu; Philip, Joel (Indian Journal of Community Health, 2020)
The concept of ‘one health’ recognizes that there is an inextricable link between the health of people, animals, and the shared environment. With the rapid growth in population and the destruction of natural habitats, humans are coming into closer contact with wild and domesticated animals. This, in turn, creates ripe conditions for the movement of viruses and diseases between animals and people. The world is seeing frequent occurrences of epidemics caused by new pathogens, to which humans have little immunity, owing to this phenomenon. ‘One Health’ assumes global significance today when the world is in the grip of the COVID-19 pandemic. The response of the state of Kerala to the COVID-19 crisis is guided by its prior experience with curbing the Nipah virus epidemic in 2018. The same core philosophy of ‘one health’ that was at the heart of the campaign to rein in the Nipah outbreak has spearheaded the state response to the COVID-19 pandemic. A review of available literature in Pubmed/Medline & Google scholar databases was carried out to study the impact of ‘one health’ on the epidemic response of Kerala state to the Nipah virus, and how it has been extrapolated in managing the current COVID-19 pandemic. The articles obtained were screened by title, abstract and full text to obtain the most relevant papers. Recommendations have also been proposed regarding the incorporation of ‘one health’ in public health strategy.